المؤرخ ابن أبي السرور البكري (ت 1087هـ) ومؤلفاته الناقلة لمنهجه التربوي: THE HISTORIAN IBN ABI AL-SURUR AL-BAKRI (D. 1087AH) AND HIS WORKS AS PROOF ON HIS EDUCATIONAL METHODS - Mahmood al-Leheabi, Saleh Muhammad Zeki; Abdul Hamid, Faisal @ Ahmad Faisal (Journal of Islamic Educational Research, 2018)
This research is part of the efforts to introduce the effects of education since childhood in the composition of people, and our example will be the historian Ibn Abi al-Surur al-Bakri (d. 1087AH) to obtain accurate information about him and highlight the importance of this historian because he enjoys special features, methodology and he has methods of his own. He was able to record information and prove his unique and distinct views. The search will focus on his tutors whom he received the knowledge from and how his methodology settled. We will confirm the names of his manuscripts and search for its whereabouts and determine the printed from the unrefined manuscripts and whether it exists or missing. The importance of this research lies in the fact that it seeks to uncover many unknown or different aspects of Ibn Abi al-Surur. It is also an attempt to guide researchers and those concerned with Islamic history with the most important works of Ibn Abi al-Surur and its whereabouts. The question that this research seeks to answer is whether Ibn Abi al-Surur has had a special mythology that he could draw from his tutors and did he actually prove that he is a distinguished historian who has his own distinguished way and how this can be concluded from his existing or lost books, and how they can be traced.